(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
By focusing on pivotal episodes such as the 1527 Giunti edition or the first English translation with the title of Canzoniere by Charles Lyell in 1835, the essay retraces the print circulation of Dante’s lyric poetry and questions the meaning of the titles chosen for the Rime, inevitably in parallel to what happens with Petrarch’s Fragmenta. The editorial history of ‘Dante’s canzoniere’, songbook (or of ‘Dante’s canzonieri’, songbooks) allows to deepen our understanding of different stages in the creation and fortune of the songbook as a literary genre, and illuminates a fertile, uninterrupted and constant interaction between contemporary and medieval lyric, as well as between poets and editors.